The woman who smashed codes : a true story of love, spies, and the unlikely heroine who outwitted America's enemies - Fagone, Jason ([New York, NY] : Dey St., an imprint of William Morrow, 2018)
In 1916, a young Quaker schoolteacher and poetry scholar named Elizebeth Smith was hired by an eccentric tycoon to find the secret messages he believed were embedded in Shakespeare's plays. She moved to the tycoon's lavish estate outside of Chicago expecting to spend her days poring through old books. But the rich man's close ties to the U.S. government, and the urgencies of war, quickly transformed Elizebeth's mission. She soon learned to apply her skills to an exciting new venture: codebreaking -- the solving of secret messages without knowledge of the key. Working alongside her on the estate was William Friedman, a Jewish scientist who would become her husband and lifelong codebreaking partner. Elizebeth and William were in many ways the Adam and Eve of the National Security Agency, the U.S. institution that monitors and intercepts foreign communications to glean intelligence. In this book, journalist Jason Fagone chronicles the life of this extraordinary woman who played an integral role in our nation's history -- from the Great War to the Cold War. He traces Elizebeth's developing career through World War I, Prohibition, and the struggle against fascism. She helped catch gangsters and smugglers, exposed a Nazi spy ring in South America, and fought a clandestine battle of wits against Hitler's Reich, cracking multiple versions of the Enigma machine used by German operatives to conceal their communications. And through it all, she served as muse to her husband, a master of puzzles, who astonished friends and foes alike. Inside an army vault in Washington, he worked furiously to break Purple, the Japanese version of Enigma -- and eventually succeeded, at a terrible cost to his personal life. Fagone unveils America's codebreaking history through the prism of one remarkable woman's life, bringing into focus the events and personalities that shaped the modern intelligence community.
Author's note: Prying eyes -- Fabyan -- Unbelievable, yet it was there -- Bacon's ghost -- He who fears is half dead -- The escape plot -- Target practice -- Grandmother died -- Magic -- The Hauptsturmführer and the Funkmeister -- Circuit 3-N -- The doll lady -- Hitler's lair -- Epilogue: Girl cryptanalyst and all that.
Includes bibliographical references (pages 347-427) and index.
Keywords: Friedman, Elizebeth, -- 1892-1980; Friedman, William F. -- 1891-1969.; Friedman, Elizebeth, -- 1892-1980.; Enigma cipher system; Cryptographers -- United States -- Biography; Cryptography -- United States -- History; Cryptography -- History; Cryptographers -- Biography; Cryptography -- United States -- History